ISO 9000 and Statistical Science (in Japanese) - Kanesan , Muthusamy; Noguchi, Hiroshi (2005)
In clause 8, measurement, analyzing and improvement for the requirement of ISO 9000, statistical practices are required. However, during the verification and validation for certification, and renewing, applicants were asked by auditors on the application of any statistical methods. Most companies admitted that no statistical methods applied and it is not necessary to utilise them. In order to improve quality, is it necessary to decide statistical methods? Drucker described in his book titled “Emerging theories of Manufacturing, Managing for the future: the 1990s and beyond“ that “statistical practices promote manufacturing technology in innovated factories and it leads to changes of social structure in these factories”. This article reviews Quality Management System (QMS) for improvement of quality, and real practices of statistical science, which required by the ISO 9000. This article also examines practices of statistical science based on the real world results and discussion with Dr. Muthusamy, who practiced Six Sigma at Motorola. (Authors' abstract)